“And your future is looking…?” “…Hopeful”: an Interpretative Phenomenological analysis study exploring the experience of school for young people of African Caribbean descent - Abijah-Liburd, Maria (2018)
This research took an Interpretative Phenomenological approach to explore the school experience of young people of African-Caribbean descent. Four young people aged 16-18 were interviewed using a semi-structured format. Data generated from the interviews were analysed using Interpretative Phenomenological Analysis. Three Master themes were drawn from the young people’s accounts; Wanting to succeed; Fitting in; and Transcending challenge. From the participants’ accounts it was interpreted that the young people valued learning, although they demonstrated differing significance that learning held for them. The young people made distinctions between schooling and education, sometimes being critical of schooling whilst continuing to value education. It was interpreted from the accounts that participants demonstrated both a desire to achieve and progress, as well as self-belief in their ability to do so. Concepts of ‘Success’ were drawn from the young people’s accounts including personal ownership of personal effort, overcoming challenge, achieving beyond expectations and aspiring to reach full potential. Agency, resilience and resistance were discernible in the young people’s accounts and revealed themselves through expressions of positive self-concept, aspiration, self determination, challenging negative expectations, growing out of experience, application of coping strategies, goal orientation and demonstrations of autonomy. The young people experienced varying degrees of fitting in to their school environment, which appeared to be mediated by how they experienced their racialised identity in their school setting, the emotional experiences they had in school and the level to which they experienced a sense of belonging. The young people who experienced a greater sense of belonging attended diverse schools, they described the sense of being one of many and experienced their schools as safe and caring places. For others, school was experienced as an uncomfortable place, wherein they experienced a sense of being ‘othered’ and of being treated unfairly. Implications for schools focus on the need to develop a positive school ethos through which young people are able to feel valued and cared for, developing understanding of the cultural and ‘racial’ dynamics at play within the school environment and how these may be experienced by pupils of African-Caribbean descent, and addressing issues of diversity in the setting. Implications for Educational Psychologists (EPs) focussed on ways in which they can apply their psychology to support schools in understanding the needs of pupils of African-Caribbean descent, however, it is also suggested that the profession participate in introspective exploration related to its understanding of inequality.